2020
DOI: 10.1002/jor.24850
|View full text |Cite
|
Sign up to set email alerts
|

Pedigree analysis of lumbar developmental spinal stenosis: Determination of potential inheritance patterns

Abstract: Lumbar developmental spinal stenosis (DSS) refers to multilevel pre‐existing narrowed spinal canals, which predispose to neural compromise. The objective of this study is to identify any inheritance pattern of DSS by utilizing pedigree charts. This was a case series of 13 families with a total of 80 subjects having magnetic resonance imaging (MRI) from L1 to S1. Cases (subjects with DSS) or controls (subjects without DSS) were identified by measuring their anteroposterior (AP) vertebral canal diameters. Multil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Kasai et al [ 10 ] studied the physical characteristics of patients with DCSS and reported on the small inter inner canthal distance on the face. Cheung et al [ 11 ] and Lai et al [ 12 ] recently proposed that DLSS may be a multifactor hereditary disease similar to hypertension, diabetes, cancer, or dementia. As a result, we concentrated on height, head size, face shape, and upper limb length as physical features that are easily influenced by genetic information, and we investigated skeletal features other than the spine in people with DCSS and DLSS.…”
Section: Introductionmentioning
confidence: 99%
“…Kasai et al [ 10 ] studied the physical characteristics of patients with DCSS and reported on the small inter inner canthal distance on the face. Cheung et al [ 11 ] and Lai et al [ 12 ] recently proposed that DLSS may be a multifactor hereditary disease similar to hypertension, diabetes, cancer, or dementia. As a result, we concentrated on height, head size, face shape, and upper limb length as physical features that are easily influenced by genetic information, and we investigated skeletal features other than the spine in people with DCSS and DLSS.…”
Section: Introductionmentioning
confidence: 99%
“…As DSS is considered to be a developmental event, 6 multilevel stenosis is expected and these patients are prone to developing neural compression at multiple levels. 7 - 9 This contributes to a high risk of reoperation up to 22% if levels with DSS are not decompressed in the initial surgery.…”
Section: Introductionmentioning
confidence: 99%